The Role of Kitchen Administrative In Procurement of Goods Operation Kitchen at Royal Tulip Gunung Geulis Hotel in Bogor - Aggy Lestari Dwi Putri; Wildan Rizky Rahardian; Nisa Rahmaniyah Utami; Tiara Indriani (Media Pendidikan Gizi dan Kuliner, 2022)
This Paper was aimed at investigating the role of administrative staff in the kitchen department at Royal Tulip Gunung Geulis Hotel in Bogor who assist chefs in the procurement process. This Final Project was carried out qualitatively. The data in this research were gathered by means of direct observation to the research site, interviews with relevant sources at the research site, library research and searching for materials via the internet. Referring to the results obtained, it may be inferred that the kitchen department shall have at least a minimum of 1 (one) person acting as administrative staff, because some hotels are widely found to have no permanent kitchen admin, such as at the Royal Tulip Gunung Geulis Hotel in Bogor. Having regard to that matter, the kitchen admin is considered more capable of controlling the procurement process in the kitchen department.